Blockchain technology development and business applications - Fong, Whye Hin (Nanyang Technological University, 2021)
Since Bitcoin’s white paper publication by Satoshi Nakamoto in 2008, blockchain-based applications have been on an upward trend, covering various areas like financial services, healthcare systems, Internet of Things (IoT), and so forth. However, as blockchain technology is still rather new there are challenges such as scalability and security problems waiting to be overcome. The report describes blockchain technology in a comprehensive manner which gives an overview of the blockchain architecture, followed by the opportunities and current applications of it in both the financial and non-financial sectors, along with its possible challenges, and how its methodology translates into code as well as for the developed web application. The project intends to bridge the gap between those unfamiliar with the technology and how it can be incorporated into businesses which might revolutionize the digital world yet enhance trust and improve cybersecurity.